Flavones and phenylpropenoids in the surface exudate of Psiadia punctulata. - Juma, B. F.; Yenesew, A.; Midiwo, J. O.; Waterman, P. G.
Three flavones, 5,7-dihydroxy-2?,3?,4?,5?-tetramethoxyflavone, 5,4?-dihydroxy-7,2?,3?,5?-tetramethoxyflavone, and 5,7,4?-trihydroxy-2?,3?,5? -trimethoxyflavone were isolated from the leaf exudate of Psiadia punctulata, together with the previously reported 5-hydroxy-7,2?,3?,4?,5?-pentamethoxyflavone and 5,7,3?-trihydroxy-2?,4?,5?-trimethoxyflavone. The two phenylpropenoids, Z-docosyl-p-coumarate and E-docosyl-p-coumarate were also isolated. The structures were determined on the basis of spectroscopic evidence. Three flavones including 1, along with a docosyl coumarate were isolated from the aerial exudate of Psiadia punctulata. The structures were established on the basis of spectroscopic information and comparison with published data.
Keywords: PSIADIA PUNCTULATA; COMPOSITAE; SURFACE EXUDATES; FLAVONES; PHENYLPROPENOIDS; 5,7-DIHYDROXY-2?,3?,4?,5?-TETRAMETHOXYFLAVONE; 5,4?-DIHYDROXY-7,2?,3?,5?-TETRAMETHOXYFLAVONE; 5,7,4?-TRIHYDROXY-2?,3?,5?-TRIMETHOXYFLAVONE; Z-DOCOSYL-P-COUMARATE